2007
DOI: 10.1111/j.1572-0241.2006.01010.x
|View full text |Cite
|
Sign up to set email alerts
|

Fibrogenesis in Crohn's Disease

Abstract: Greater understanding of the biology of fibrostenosis is likely to yield significant advances in our ability to care for patients with stricturing CD. Potential dividends of this approach include identification of novel therapeutic targets and biomarkers useful for prognostication and therapeutic monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
222
0
7

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(238 citation statements)
references
References 128 publications
(127 reference statements)
9
222
0
7
Order By: Relevance
“…34 Additionally, CB2 knockout mice are more sensitive than wild-type littermates to bleomycin-induced dermal fibrosis. 35 As > 30 % of patients with Crohn ' s disease develop intestinal fibrosis leading to stricture formation, frequently requiring surgical resection, 36 and myofibroblasts are key cells in the process of wound healing and stricture formation in the gut, 37 we investigated the in vitro effects of MAEA on myofibroblasts isolated from intestinal Crohn ' s disease strictures. We found that MAEA reduced collagen production by strictured Crohn ' s disease myofibroblasts and increased their migration ability, thus supporting the view that endocannabinoid pathways might be involved in the fibrogenic process in Crohn ' s disease.…”
Section: Articlesmentioning
confidence: 99%
“…34 Additionally, CB2 knockout mice are more sensitive than wild-type littermates to bleomycin-induced dermal fibrosis. 35 As > 30 % of patients with Crohn ' s disease develop intestinal fibrosis leading to stricture formation, frequently requiring surgical resection, 36 and myofibroblasts are key cells in the process of wound healing and stricture formation in the gut, 37 we investigated the in vitro effects of MAEA on myofibroblasts isolated from intestinal Crohn ' s disease strictures. We found that MAEA reduced collagen production by strictured Crohn ' s disease myofibroblasts and increased their migration ability, thus supporting the view that endocannabinoid pathways might be involved in the fibrogenic process in Crohn ' s disease.…”
Section: Articlesmentioning
confidence: 99%
“…Treatment associated with a reduction of the fraction of circulating CCR9-positive T cells producing interferon-γ or IL-17A, a subset of inflammatory T cells with gut-homing properties, which are increased in active CD [41,42]. Since TGF-β1 has pro-fibrogenic effects and CD natural history can be marked by the development of fibrostrictures [43], all the patients receiving Mongersen were monitored for the development of such a complication. No patient developed strictures or obstructive symptoms during the study nor had a significant increase in the serum levels of fibrogenic markers [44].…”
Section: Mongersen: the Clinical Relevance Of Smad7 Inhibitionmentioning
confidence: 99%
“…Some researchers have previously shown that inducible NO synthase (iNOS) expression was significantly elevated in STZ diabetic rat hearts [22] and once induced, iNOS is known to generate large amounts of NO until the enzyme is degraded [23]. Some cytokines, as example IGF-I, TGF-β1, connective tissue growth factor, platelet-derived growth factor, basic fibroblast growth factor, and epidermal growth factor, have been reported to both increase cellular proliferation (intestinal smooth muscle cells or myofibroblasts) and increase synthesis of ECM or collagen [24,25].…”
Section: Introductionmentioning
confidence: 99%